2021
DOI: 10.1145/3479526
|View full text |Cite
|
Sign up to set email alerts
|

Digital Privacy Perceptions of Asylum Seekers in Germany: An Empirical Study about Smartphone Usage during the Flight

Abstract: Since 2015, an increased number of asylum seekers is coming to Europe. These migration movements increasingly rely on digital infrastructure, such as mobile internet access and online services, in order to reach their targeted destination countries. Asylum seekers often use smartphones for information and communication purposes. Even though there are many positive aspects in the use of such technologies, researchers have to consider the perceived risks of this specific user group. This work aims at investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Difficulty in navigating the chatbot partly stems from participants' lack of digital literacy, which can be attributed to the violence-induced lack of education in Afghanistan. Digital illiteracy is also observed in Steinbrink et al (2021), who demonstrated that Afghan refugees in Germany have particularly low digital literacy compared to other nationalities. However, the design of the chatbot also produced barriers.…”
Section: Digital Illiteracymentioning
confidence: 84%
“…Difficulty in navigating the chatbot partly stems from participants' lack of digital literacy, which can be attributed to the violence-induced lack of education in Afghanistan. Digital illiteracy is also observed in Steinbrink et al (2021), who demonstrated that Afghan refugees in Germany have particularly low digital literacy compared to other nationalities. However, the design of the chatbot also produced barriers.…”
Section: Digital Illiteracymentioning
confidence: 84%
“…Previous research has proposed that the "average user" might actually be a myth and that users differ substantially in their privacy preferences and needs [2,5,13,16,56]. There are also highly diverse usage contexts resulting in different requirements [32,55]. Therefore, it is crucial to take into account inter-individual differences and different groups of end-users if truly effective support is to be provided.…”
Section: The Role Of Personalisationmentioning
confidence: 99%
“…The research community elucidates the social and networked nature of privacy, critically examining the implications of sociotechnical systems on individual collaborators’ (Wardrip et al , 2013), experts (Emami Naeini et al , 2018) and users’ (Badillo-Urquiola et al , 2018), as well as on communities’ privacy (Khojasteh et al , 2019) as experienced. Studies also illustrate the challenges associated with the collection of rich qualitative details to provide insight into the contextual experiences and nuance of examples relative to privacy, documenting mechanisms for rigor with small samples (Steinbrink et al , 2021), especially in conjunction with multimethod designs (Steinbrink et al , 2021; Wardrip et al , 2013). Our work continues this thread by investigating understudied elements of the higher education technology ecosystem.…”
Section: Background and Related Workmentioning
confidence: 99%